Can sprouting reduce phytate and improve the nutritional composition and nutrient bioaccessibility in cereals and legumes?. Issue 2 (21st April 2022) - Elliott, Hannah; Woods, Patrick; Green, Brian D.; Nugent, Anne P.
Abstract: Sprouting is a traditional processing method which has been used for centuries to improve the nutritional value of cereals and legumes. There has been growing interest in sprouted products in recent years due to a high demand for more natural and healthy foods. Phytate is the primary storage form of phosphorus in plants. It is long recognised to affect human health as it forms insoluble complexes with minerals such as iron and zinc in cereals and legumes, thereby preventing their absorption in the body. Sprouting activates the enzyme phytase, which degrades phytate, thereby improving mineral bioaccessibility and bioavailability. The extent of phytate reduction varies depending on the sprouting conditions, cereal/legume species, cultivar and native phytase activity. Sprouting has been associated with increased iron, zinc and calcium bioaccessibility in many studies, but this appears to differ in cereals and legumes, which possibly is due to the presence of other 'antinutrients'. Protein digestibility also appears to be positively correlated with phytate reduction albeit less than for minerals. It is not possible to accurately predict the influence of sprouting on nutrient bioavailability because so few studies have been conducted. Further research is required to determine whether the commercial production of sprouted cereals and legumes can increase the nutritional value and health benefits of commercial end products.